Classifying Work in the New Economy - Cappelli, Peter; Keller, JR (Academy of Management Review, 2013)
Alternatives to the archetypal model of full-time regular employment are now both prevalent and wide-ranging. Over a fifth of U.S. workers, and even more globally, now perform economic work under arrangements that differ from full-time regular employment. Yet most of our management and social science notions about economic work are based on the full-time employment model. We know relatively little about the operation and consequences of alternative arrangements in part because while these arrangements vary considerably, they are commonly grouped together for research purposes using existing classification systems. We outline an inclusive classification system that distinguishes clearly between employment and its alternatives. It also distinguishes among the alternatives themselves by grouping work arrangements into categories that share common properties and that are distinct from each other in ways that matter for practice and for research. The classification system is based on distinctions about the sources and extent of control over the work process, the contractual nature of the work relationship, and the parties involved in the work relationship. Our classification system is both informed by and reflects the legal distinctions among these categories. We explore implications of our system for research and theory development.